Studi Analisis Disparitas Putusan Mahkamah Agung Atas Pembatalan Merek Terkenal Untuk Barang Tidak Sejenis; Perbandingan Kasus Merek SKYWORTH dengan Merek BMW - Widya Novita; Soefyanto Soefyanto; Andi Syafrani (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to determine the disparity in the Supreme Court's decision on the cancellation of famous brands for non-similar goods in the SKYWORTH Brand case with the BMW Brand. The problems related to disparity in cancellation of trademark registration applied by the Supreme Court as outlined in the Supreme Court decision Number: 32 PK / Pdt.Sus-HKI / 2018 and the Supreme Court decision Number: 29 PK / Pdt.Sus-HKI / 2016 related to the protection of famous brands for non-identical types of goods, as well as about how the legal protection of famous brands for non-similar kind of goods This research method uses a normative juridical approach by analyzing decisions and relating to laws and regulations in the field of Trademark Law. The results of this study indicate that the factors considered by the Judges in deciding the cancellation of trademark registration that cause disparities are, the guidance of some judges in Article 6 Paragraph (2) of Law Number 15 Year 2001 Concerning Trademarks and partly guided by Article 16 Paragraph (3) TRIPs Agreement.Keywords: Disparity, cancellation of trademark registration, famous trademark, Non-identical goods, Supreme Court.